(untitled) (Journal of Business Management and Accounting, 2025)
While financial well-being among Malaysians is improving due to coordinated efforts by the government and various stakeholders, notable gaps remain, such as poor money management habits and high debt levels, especially among the younger generation. These challenges are largely attributed to limited financial literacy, especially concerning financial awareness. This study seeks to shed light on the financial insights of young Malaysians by exploring the relationships between financial awareness, knowledge, attitudes, behaviors, and financial well-being. An online survey was carried out to gather data. The study utilized partial least squares structural equation modeling (PLS-SEM) to test its hypotheses, engaging 197 respondents. The findings revealed that individuals with strong financial knowledge, shaped by their financial awareness, possess significantly positive financial attitudes and behaviors, ultimately leading to enhanced financial well-being. The study provides meaningful perspectives that can enrich theoretical frameworks surrounding financial literacy, emphasizing the need for a multifaceted approach to promoting financial well-being. The study also offers invaluable information for the government, government agencies, educational institutions, and other stakeholders, to further advance efforts in raising financial awareness. Empowering young adults with financial literacy, encompassing financial awareness, knowledge, attitude, and behavior, is essential for improving the overall financial well-being of Malaysians and addressing the persistent knowledge gap in the country. However, the primary focus should be on continuously reinforcing awareness within this demographic to bridge the knowledge gap.